Islamic banking and finance an introduction - Haniffa, Roszaini; Hudaib, Mohammad (Cengage Learning EMEA, 2019)
This text provides a comprehensive introduction to the practice of Islamic banking and finance, an increasingly important area in the field of Finance. The authors cover current issues and concepts pertinent to Islamic finance, from the Islamic worldview and economics, to Shariah compliance, Islamic contracts and insurance.